Problems and solutions for college chemistry and general chemistry - John H Meiser (D. C. Health, 1984)
the book involves discussion of concepts of chemistry requiring specific use of mathematics. Each unit begins with a short introduction to the particular subject area. A detailed section on definitions and formulas pertinent to that subject area and the exercises with their solutions follow. The book also contains a self-instructional section that teaches the use of exponential numbers and logarithms